A COLLABORATIVE CHARACTER DEVELOPMENT OF PRIMARY SCHOOL STUDENTS IN LEARNING USING THE RADEC MODEL - Nurnaningsih, Nurnaningsih; Syaodih, Ernawulan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The collaboration is crucial in the world of education and work, to teach it there needs to be implications for innovation through appropriate learning models. The RADEC learning model is one of the solutions to the difficulties of developing collaborative character. This study aims to determine the form of student collaboration characters using the RADEC learning model. This research involved 34 students in an elementary school in the city of Bandung. Qualitative descriptive method used in this study. Researchers as key instruments and data collection techniques used by observation. This study obtained findings, among others, that the character of student collaboration appears in the form of indicators that appear in students.